How Understanding-Based Redesign Influences the Pattern of Actions and Effectiveness of Routines. (May 2019) - Bapuji, Hari; Hora, Manpreet; Saeed, Akbar; Turner, Scott
Using a novel, mixed-methods research design, we examine how understanding-based redesign of a routine influences its effectiveness. By understanding-based redesign, we refer to an intentional change in routine design such that it aligns more closely with the understandings of participants regarding how to perform their roles in the routine. We argue that this type of redesign improves the effectiveness of a routine by facilitating the actions and interactions of routine participants. Our empirical examination focused on manipulating the procedure and physical artifacts available for performing the towel-changing routine at a hotel. Through a field experiment, we found that understanding-based redesign results in greater effectiveness of the routine, and based on a qualitative, interviews-based inquiry with key participants in the routine, we propose six processes by which understanding-based redesign influences participant actions that support routine effectiveness. Our study offers important implications for strategy and organizations research on routines, as well as useful implications for management practice.